The Mark-to-Market Valuation and Executive Pay Package Regulations within the 2009 US (Bailout) Emergency Economic Stabilization Act - Haidar, Jamal Ibrahim (2012)
The paper shows that the effect of the Emergency Economic Stabilization Act (EESA) is ambiguous. It discusses the benefits and costs of mark-to-market valuation and design of executive pay package policies within the US 2009 EESA. It highlights how the mark-to-market valuation standard influenced financial institutions, explains why mark-to-market policy suspension proponents can support the EESA, and realizes how the Financial Accounting Standards Board (FASB) and Securities Exchange Commission (SEC) can count on the EESA while assessing the need and cost of the mark-to-market policy. Also, the paper discusses the promise of executive wage caps within the EESA. Moreover, it differentiates between executive pay packages pre- and post-EESA policies.